Modelling and Analysis of the Dynamic Behavior of a Double Cylinder Inline 650cc Gasoline Engine with Crank Angle 0o for Rubber Mount - Harus Laksana Guntur; Karina Yulia (IPTEK Journal of Proceedings Series, 2014)
This paper presents a numerical study and analysis of the dynamic behavior of a double cylinder inline 650cc gasoline engine with crank angle 0o for rubber mount. Numerical study was done by mathematically modeling a double cylinder inline 650cc gasoline engine with crank angle 0o for rubber mount and simulating its dynamic behavior for 3 different connecting rod lengths:115.6mm, 125.6mm, and 135,6mm. Its mathematical model was developed from the physical model of engine produced by local manufacturer. All parameters used in the simulation are based on the engine specification provided by the manufacturer. In the mathematical model, connecting rod length was varied to investigate its influence to the engine’s dynamic behavior. Here, the engine system was modeled as a spring-mass-damper system excited by a periodic force produced by the cylinder working pressure with various excitation frequencies from 1000rpm to 5000rpm. The engine’s dynamic behavior was indicated by vertical motion (bouncing) and angular motion (pitching) of the engine mass, which is presented in displacement, velocity and acceleration. The results show that connecting rod length does not influence the engine’s dynamic behavior. Further, the increase in engine’s angular speed/excitation frequency influence significantly the engine’s dynamic behavior. The detail results of this study are reported and discussed in the paper.